Dietary Fiber Supplements: Effects in Obesity and Metabolic Syndrome and Relationship to Gastrointestinal Functions - Papathanasopoulos, Athanasios (2009)
Dietary fiber (DF) is a term that reflects to a heterogenous group of natural food sources, processed grains and commercial supplements. Several forms of DF have been used as complementary or alternative agents in the management of manifestations of the metabolic syndrome, including obesity. Not surprisingly, there is a great variation in the biological efficacy of DF in metabolic syndrome and body weight control. Diverse factors and mechanisms have been reported as mediators of the effects of DF on the metabolic syndrome and obesity. Among this array of mechanisms, the modulation of gastric sensorimotor influences appears to be crucial for the effects of DF, but also quite variable. This article focuses on the role, mechanism of action and benefits of different forms of fiber and supplements on obesity and metabolic syndrome, glycemia, dyslipidemia, cardiovascular risk, and explores the effects of DF on gastric sensorimotor function and satiety in mediating these actions of DF.